(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
Hairspray is widely used worldwide in beauty salons and barbershops to create customized hairstyles. However, the chemicals in hairspray are highly flammable, posing significant risks of burn injuries to staff and customers, especially when clothing is exposed to heated tools such as hairdryers or curling irons. Hairsprays typically contain polymer-based adhesives, liquid solvents, and propellant gases. During application, a notable amount of overspray can settle on clothing, depositing a thin adhesive layer on the fabric. This research project aimed to assess how exposure to hairspray alters the flammability of different fabric types, including Silk, Cotton, Wool, Nylon, and Polyester. Fifteen fabric samples were treated with hairspray, while another fifteen samples served as untreated controls. All treated samples were exposed to the same amount of hairspray and left to dry for 24 hours, while the control samples remained untouched. Flame temperatures and total burn times were measured during testing. The findings revealed that the maximum flame temperatures for Polyester increased by 140%, with burn times rising by 74%. For Nylon, flame temperatures rose 178%, and burn times increased 75%. In contrast, the flame temperatures and burn times for Silk, Cotton, and Wool remained unchanged. The results of further analysis using differential scanning calorimetry and Raman Microspectroscopy suggested that the flammability differences between natural and synthetic fibres are linked to fibre polarity and hydrophobicity variations.